2021
DOI: 10.3390/molecules26154622
|View full text |Cite
|
Sign up to set email alerts
|

Square-Planar Heteroleptic Complexes of α-Diimine-NiII-Catecholate Type: Intramolecular Ligand-to-Ligand Charge Transfer

Abstract: Two heteroleptic NiII complexes combined the redox-active catecholate and 2,2′- bipyridine ligand platforms were synthesized to observe a photoinduced intramolecular ligand-to-ligand charge transfer (LL’CT, HOMOcatecholate → LUMOα-diimine). A molecular design of compound [NiII(3,6-Cat)(bipy)]∙CH3CN (1) on the base of bulky 3,6-di-tert-butyl-o-benzoquinone (3,6-DTBQ) was an annelation of the ligand with an electron donor glycol fragment, producing derivative [NiII(3,6-Catgly)(bipy)]∙CH2Cl2 (2), in order to infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 76 publications
(160 reference statements)
3
24
0
Order By: Relevance
“…The vast class of CT colorants is presented by transition metal complexes, the metal-to-ligand charge transfer (MLCT) of which is facilitated by non-planar molecular geometry [ 30 , 31 ] with high coordination numbers, and driven by a pronounced back donation phenomenon [ 32 ]. Remarkably, the molecular design of highly effective MLCT dyes derived from Mo [ 27 ], Os [ 4 , 6 ], Re [ 4 , 6 , 33 ], and mainly Ru [ 4 , 6 , 27 , 34 , 35 ] has been named an absolute priority, which can be explained by their use as photosensitizers (otherwise “redox mediators” [ 36 ]) in photovoltaic (PV) devices of Grätzel cell’s type [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The vast class of CT colorants is presented by transition metal complexes, the metal-to-ligand charge transfer (MLCT) of which is facilitated by non-planar molecular geometry [ 30 , 31 ] with high coordination numbers, and driven by a pronounced back donation phenomenon [ 32 ]. Remarkably, the molecular design of highly effective MLCT dyes derived from Mo [ 27 ], Os [ 4 , 6 ], Re [ 4 , 6 , 33 ], and mainly Ru [ 4 , 6 , 27 , 34 , 35 ] has been named an absolute priority, which can be explained by their use as photosensitizers (otherwise “redox mediators” [ 36 ]) in photovoltaic (PV) devices of Grätzel cell’s type [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, CT chromophores of D-M II -A type (often this is dye with ligand-to-ligand charge transfer (LL’CT) and less coordination numbers) can provide a competitive alternative towards MLCT colorants due to noteworthy aspects: (1) pronounced charge separation on a molecular level with a planar mutual arrangement of interacting HOMO (donor organic part) and LUMO (acceptor organic part) [ 32 ]; (2) higher intense absorptivity; (3) an ability to fine-tune CT energy in the course of molecular design, varying electronic properties of ligands by functionalization; (4) lower energy of effective intramolecular CT in some cases, leading to an absorption/emission even in the NIR region [ 29 ] of an undeniable practical importance. It should be noted that a diminution in CT energy up to NIR absorption/emission is one of the priority tasks in the colorant chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examining the geometrical structure of most Pd-complexes, it was found that 4-bonded coordinated structure locate between tetrahedral and square planar geometrical pathway depending on the electronic con guration of the metal. Also, a mutual arrangement around the planar environment basically depends the interacting molecular orbitals resulting the implementation of optimal planar geometry of the compound causing ligand-ligand charge transfer reactions [15][16][17] To view of mentioned above, researches move towards the molecular design study of many metal complexes preferring the square-planar structure.…”
Section: Introductionmentioning
confidence: 99%